Structural, microstructural, magnetic and dielectric properties of Fe2O3 modified CuO composite - Rajnish Grewal; Sunita Dahiya; Sunil Kumar; Naveen Kumar (Zaštita Materijala)
1-xCuO-xFe2O3 composites where x = 0.05, 0.10, 0.15 and 0.20 have been synthesized using ball milling mixing method. The structural, microstructural, elemental analysis, magnetic and dielectric properties of prepared ceramic composites have been investigated using the advanced characterization techniques. The influence of sintering temperature on structural, dielectric and magnetic properties have been investigated. The structural phase analysis has been carried out using X-ray diffraction and effect of sintering temperature clearly depicted in graphs. As increase in sintering temperature from 700 °C to 900 °C, diffraction peaks shift towards higher angles, indicating changes in crystal lattice parameters and potential crystal structure distortions. However, after careful consideration of the XRD results and a comprehensive analysis, we concluded that a synthesis temperature of 700 °C is preferable. The SEM micrographs shows an increase in grain size of ceramic composites as concentration of Fe2O3 increases. The Energy Dispersive X-Ray spectroscopy affirms presence of elements according to stoichiometric proportion whereas S-shaped M vs. H. loop confirms presence of magnetic ordering. Variation of Real (ε') and Imaginary (ε") parts of dielectric permittivity with frequency shows general dielectric behavior.